Assentamento de reforma agrária na região do Pontal do Paranapanema e seus impactos econômicos e sociais. - Pimentel, Andréa Eloísa Bueno (2004)
The purpose of this thesis is to analyze the agrarian reform in the land settlements in the region of Pontal do Paranapanema and its economic and social impact. The field research was elaborated through the comparison of four towns where there are land settlements reforms and four towns with similar dimensions and characteristics, where there any kind of land settlement. The chosen towns with land settlements were: Mirante do Paranapanema, Euclides da Cunha Paulista, Teodoro Sampaio and Rosana. The towns without land settlements whose data were used for comparison are: Santo Anastácio, Álvares Machado, Pirapozinho and Regente Feijó, all belonging to Presidente Prudente government. As stated hypothesis, there are, firstly, that the formation of agrarian land settlements causes positive economic impact in the towns or regions where they are located, while the internal profits are used inside the domestic trade and consequently, the taxes collection in the borough is enlarged. Secondly, the economic changes inside these land settlements also generate social impact around it, with improvement in the municipal substructure, derived from the new demands over public services as well as from the power originated under the land settlers vindication. The results direct to the settles better life quality concerning to the housing features, access to water and electrical energy, machinery acquisition, agricultural implement and electronics as well the raise of some taxes and the increase on the number of all kinds of trade. However, the low production diversity associated to the low production for the self consumption tend to be a negative factor for the regional land settlers. It s necessary to form a strong social structure between the settlers that can aim its power as a formed group, its technical qualification, (Cocamp) Cooperative empowerment and efficient agri industry operation besides the landed regulation of Pontal do Paranapanema region.